The Effect of Education Level, Economic Growth, Allocation of Government Expenditure, and The Number of Poor People on Unemployment In Bali Province In 2017-2020 - Nico Candra Pratama; Maulidyah Indira Hasmarini (Journal Research of Social Science, Economics, and Management, 2022)
The purpose of this study is to measure the direction and magnitude of the influence of education levels, economic growth, allocation of government expenditure, and the number of poor people unemployed in Bali in 2017-2020. The analysis method used is the Panel Least Square (PLS) regression method with cross sections covering 8 regencies and 1 city in Bali province, namely: Jembrana Regency, Tabanan Regency, Badung Regency, Gianyar Regency, Klungkung Regency, Bangli Regency, Karangasem Regency, Buleleng Regency, Denpasar City. And this research uses a time series starting from 2017-2020. Independent variables used to explain the factors influencing the unemployment rate are the level of education, economic growth, goverment expenditure allocation, and the number of poor people.